2010
DOI: 10.18388/abp.2010_2382
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis is a risk factor for celiac disease.

Abstract: The coexistence of cystic fibrosis (CF) and celiac disease (CD) has been reported. To our knowledge there is no study directly comparing the incidence of CD in CF patients to that in the general population at the same time. There is no published data on genetic predisposition to CD in CF patients either. Therefore, in the present study we aimed to assess the genetic predisposition to CD and its incidence in CF patients comparing it to data from the general population. Two hundred eighty-two CF patients were en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(51 citation statements)
references
References 32 publications
3
43
0
3
Order By: Relevance
“…HLA-DQA1 and HLA-DQB1 are likely genetic markers of the Celiac Disease [71] which was suggested to be a risk factor in CF [72, 73]. Therefore, together with our present results, we propose HLA-DQA1 and HLA-DQB1 genes, as new modifiers in CF.…”
Section: Resultssupporting
confidence: 79%
“…HLA-DQA1 and HLA-DQB1 are likely genetic markers of the Celiac Disease [71] which was suggested to be a risk factor in CF [72, 73]. Therefore, together with our present results, we propose HLA-DQA1 and HLA-DQB1 genes, as new modifiers in CF.…”
Section: Resultssupporting
confidence: 79%
“…An approximately threefold increase in the prevalence of fully diagnosed CD, as well as a ~ 4% prevalence of positive anti‐TG2‐IgA autoantibodies, a serological marker of CD, even in the absence of villous atrophy (Lionetti et al , ), has been reported in several cohorts of patients with cystic fibrosis (CF; Fluge et al , ; Walkowiak et al , ; De Lisle & Borowitz, ), including ours (Appendix Table S1). CF is the most frequent monogenic lethal disease worldwide (Cutting, ) , caused by loss‐of‐function mutations of the gene coding for cystic fibrosis transmembrane conductance regulator (CFTR), a cyclic adenosine monophosphate (cAMP)‐regulated anion channel that mediates chloride/bicarbonate transport across epithelia (Gadsby et al , ; Cutting, ).…”
Section: Introductionsupporting
confidence: 57%
“…The authors postulated that intestinal inflammation, exocrine pancreatic insufficiency leading to protein exposure, and a shorter time of breast feeding may predispose genetically CF patients to celiac disease. 10 Indeed, children with CF have increased intestinal inflammatory markers, including eosinophilic cationic protein and neutrophil elastase. 11 Evidence also suggests that complementary food avoidance before 4 months of age allows breast milk to provide immunologic protection from celiac disease in genetically at-risk individuals.…”
Section: Discussionmentioning
confidence: 99%